An external quantum efficiency of >20% from solution-processed poly(dendrimer) organic light-emitting diodes. (December 2018) - Maasoumi, Fatemeh; Jansen-van Vuuren, Ross; Shaw, Paul; Puttock, Emma; Nagiri, Ravi; McEwan, Jake; Bown, Mark; O'Connell, Jenny; Dunn, Christopher; Burn, Paul; Namdas, Ebinazar
Abstract Controlling the orientation of the emissive dipole has led to a renaissance of organic light-emitting diode (OLED) research, with external quantum efficiencies (EQEs) of >30% being reported for phosphorescent emitters. These highly efficient OLEDs are generally manufactured using evaporative methods and are comprised of small-molecule heteroleptic phosphorescent iridium(III) complexes blended with a host and additional layers to balance charge injection and transport. Large area OLEDs for lighting and display applications would benefit from low-cost solution processing, provided that high EQEs could be achieved. Here, we show that poly(dendrimer)s consisting of a non-conjugated polymer backbone with iridium(III) complexes forming the cores of first-generation dendrimer side chains can be co-deposited with a host by solution processing to give highly efficient devices. Simple bilayer devices comprising the emissive layer and an electron transport layer gave an EQE of >20% at luminances of up to ≈300 cd/m2, showing that polymer engineering can enable alignment of the emissive dipole of solution-processed phosphorescent materials. Efficient OLEDs from solution: engineering dipole alignment in polymers Dipole alignment is achieved in efficient solution-processed organic light-emitting diodes featuring a novel poly(dendrimer). A collaborative team led by Paul Burn from the Centre for Organic Photonics & Electronics, School of Chemistry & Molecular Biosciences at The University of Queensland have developed solution-processed organic light-emitting diodes (OLEDs) based on a phosphorescent poly(dendrimer)-based material with an out-coupling efficiency of around 40% and an external quantum efficiency of above 20%. The key to the enhanced light out-coupling in the devices is the favourable alignment of emissive dipoles in the poly(dendrimer), which consists of dendritic side-chains comprised of hole-transporting carbazole-based dendrons and iridium(III) complex-cores. The poly(dendrimer) is blended with a host material to ensure high efficiency in the device. Ultimately, the intelligent design of the developed poly(dendrimers) allowed the authors to utilise a simple bilayer device structure to demonstrate highly efficient solution-processed organic light-emitting diodes.